The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.bjoms.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods applied to audit of surgical outcomes after treatment for cancer of the head and neck

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…ML is increasingly used in the medical community, particularly in the field of oncology. Previous studies have demonstrated that ML models can provide better accuracy and discrimination for the prediction of prognoses for lung adenocarcinoma (12) and breast cancer (13), chemoradiation therapy response in rectal cancer (14), radiotherapy response for acromegaly (15), surgical outcomes for head and neck cancer (16), and diagnosis for leukemia (17). For sellar region tumors, ML could be more effective for predicting a patient's clinical outcome and could provide better clinical decision support for neuroendocrinologists and neurosurgeons (18).…”
Section: Introductionmentioning
confidence: 99%
“…ML is increasingly used in the medical community, particularly in the field of oncology. Previous studies have demonstrated that ML models can provide better accuracy and discrimination for the prediction of prognoses for lung adenocarcinoma (12) and breast cancer (13), chemoradiation therapy response in rectal cancer (14), radiotherapy response for acromegaly (15), surgical outcomes for head and neck cancer (16), and diagnosis for leukemia (17). For sellar region tumors, ML could be more effective for predicting a patient's clinical outcome and could provide better clinical decision support for neuroendocrinologists and neurosurgeons (18).…”
Section: Introductionmentioning
confidence: 99%
“…Two other groups have applied ML models to predict LOS after major HNC surgery. Tighe et al used several ML models across a multicenter cohort to predict LOS less than 15 or 20 days 24 . Limited predictors were included, and sparse details were provided regarding which predictors were significant.…”
Section: Discussionmentioning
confidence: 99%
“…They include age, baseline creatinine, monocyte count, and duration of surgery. Older age is a known characteristic for predicting prolonged LOS for patients undergoing head and neck surgery 2,24 . Creatinine may be a surrogate factor for patient comorbidities and has been shown to be a predictor of medical complications in other surgical populations 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarise results by presenting the 'champion models' of four metrics: complications within 30 days; severe complications (Clavien-Dindo >3) within 30 days; length of hospital stay (days); and positivity of surgical margins (Table 2). Further details, including calibration test results, are included in their respective publications (10)(11)(12) and model outputs (Supplementary Material 1-4).…”
Section: Methodsmentioning
confidence: 99%